2013
DOI: 10.1016/j.neuroscience.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Corticokinematic coherence during active and passive finger movements

Abstract: Corticokinematic coherence (CKC) refers to coupling between magnetoencephalographic (MEG) brain activity and hand kinematics. For voluntary hand movements, CKC originates mainly from the primary sensorimotor (SM1) cortex. To learn about the relative motor and sensory contributions to CKC, we recorded CKC from 15 healthy subjects during active and passive right index-finger movements. The fingertip was either touching or not touching table, resulting in active-touch, active-no-touch, passive-touch, and passive-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
126
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(141 citation statements)
references
References 39 publications
15
126
0
Order By: Relevance
“…Recent CKC studies also detected the coupling between the cortex and finger at the low-frequency band of repetitive finger movements (Piitulainen et al, 2013a(Piitulainen et al, , 2013bBourguignon et al, 2015). These studies concluded that SM1 was primarily activated by proprioceptive reafferents.…”
Section: Generator Mechanism Of the Low-cmcmentioning
confidence: 90%
See 2 more Smart Citations
“…Recent CKC studies also detected the coupling between the cortex and finger at the low-frequency band of repetitive finger movements (Piitulainen et al, 2013a(Piitulainen et al, , 2013bBourguignon et al, 2015). These studies concluded that SM1 was primarily activated by proprioceptive reafferents.…”
Section: Generator Mechanism Of the Low-cmcmentioning
confidence: 90%
“…Moreover, the effect of cutaneous sensation was insignificant in the present study. Piitulainen et al (2013a) reported that finger CKC is mainly due to the proprioception from finger muscle spindles during flexion-extension movements, with cutaneous inputs having a negligible effect. The authors suggested that this is because ''gating'' of cutaneous inputs occurred during finger movements, which was indicated by the fact that the intensities of cutaneous stimuli were perceived as being weaker (Milne et al, 1988), with higher perceptual thresholds (Angel and Malenka, 1982).…”
Section: Generator Mechanism Of the Low-cmcmentioning
confidence: 99%
See 1 more Smart Citation
“…Our method could however apply to cortex-muscle coherence Salenius et al, 1997Salenius et al, , 1996, corticokinmeatic coherence with active, passive or observed movements (Bourguignon et al, , 2012(Bourguignon et al, , 2011Jerbi et al, 2007;Marty et al, 2015;Piitulainen et al, 2015Piitulainen et al, , 2013aPiitulainen et al, , 2013b, and brain connectivity obtained with seed-based correlation or coherence (Brookes et al, 2012;de Pasquale et al, 2010;Hipp et al, 2012;Wens et al, 2014aWens et al, , 2014b. Also, we have demonstrated that our method of location comparison works with power-ratio maps, although it is too conservative in that context.…”
Section: Perspectivesmentioning
confidence: 98%
“…One recently introduced method for such purposes is corticokinematic coherence (CKC), the Page 6/35 coupling between MEG signals and hand kinematics during fast repetitive active and passive hand movements (Bourguignon et al, 2011(Bourguignon et al, , 2013Piitulainen et al, 2013aPiitulainen et al, , 2013b. CKC peaks at movement frequency (and its first harmonic) and its main cortical sources lay in the primary sensorimotor (SM1) cortex, contralateral to the moved hand (Bourguignon et al, 2011(Bourguignon et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%